2022
DOI: 10.1002/lom3.10496
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of methods for automated devices: A systematic review and recommendation for studies using FlowCam for phytoplankton

Abstract: Accurate and detailed reporting of methods is essential for scientific progress, yet it is widely accepted that authors across all scientific fields tend to provide insufficient methods detail. Given the recent proliferation of automated and semi‐automated technologies for data collection, to address this widespread issue the details needed for interpretation and reproducibility for each specific technique first need to be identified. A systematic literature review assessed the comprehensiveness of method deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 189 publications
0
7
0
Order By: Relevance
“…Approximately 25 mL of seawater was collected from each sample and processed with the FlowCam. All necessary settings for reproducing the FlowCam workflow are described below (Owen et al 2022). The whole water samples were analyzed using a Portable Series FlowCam with a peristaltic pump set to autoimage mode using a ×10 objective with a standard 100 μ m glass flow cell installed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 25 mL of seawater was collected from each sample and processed with the FlowCam. All necessary settings for reproducing the FlowCam workflow are described below (Owen et al 2022). The whole water samples were analyzed using a Portable Series FlowCam with a peristaltic pump set to autoimage mode using a ×10 objective with a standard 100 μ m glass flow cell installed.…”
Section: Methodsmentioning
confidence: 99%
“…There has been substantial research comparing results from advancing methods for phytoplankton community composition analysis to results from traditional light microscopy techniques (Stern et al 2018; Owen et al 2022). Studies comparing phytoplankton cell abundance results for FlowCam and light microscopy concluded that the two methods yield comparable results for quantitative abundance (Álvarez et al 2014; Bergkemper and Weisse 2018).…”
mentioning
confidence: 99%
“…This tube was selected because it covers the most dominant sizes of colonies that are found in water 35 . Therefore, colonies that are larger than 100 µm were excluded by filtering the sample to prevent clogging of particles in the filter tube 42 . A minimum of 2000 photo images were captured in each water sample from the sampling site.…”
Section: Methodsmentioning
confidence: 99%
“…Ref. [ 126 ] systematically reviews articles from 2017 to 2020 using the commercial device FlowCam for phytoplankton research. For this reason, in this review, we will focus only on novel proposals of the last five years.…”
Section: Phytoplankton Microfluidic Technologiesmentioning
confidence: 99%